Deixis Analysis Found In â€œBird Boxâ€ Movie - Natalia Rebong; Nurma Dhona Handayani (Institut Agama Islam Negeri Palopo, 2023)
Deixis is part of pragmatics that people make in communication. In this research, the researchers analyzed deixis in utterances and the movie â€œBird Boxâ€ is data source. The movie is 2018 horror movie that has deixis in the movie. The researchers analyze all utterances in the movie. This descriptive qualitative research found out types deixis in utterances of characters. The researchers used observational method with the technique of non-participatory. The pragmatic identity method with competence- in equalizing were used by the researchers. Then, the researchers use the theory from Yule (2017) to analyze deixis types that characters make. The findings show that deixis were used in the communication of the movie. There were totally 34 deixis data in spatial deixis, temporal deixis, and person deixis. 16 were in spatial deixis, 12 data in person deixis, and 6 data in the temporal deixis. The dominant is spatial deixis used by the characters to point places to other hearers in Bird Box movie.